IMPLEMENTASI KRIPTOGRAFI MENGGUNAKAN METODE BLOWFISH DAN BASE64 UNTUK MENGAMANKAN DATABASE INFORMASI AKADEMIK PADA KAMPUS AKADEMI TELEKOMUNIKASI BOGOR BERBASIS WEB-BASED - Rifa’i, Annas; Sumartini, Lilis Cucu (Politeknik Dharma Patria Kebumen, 2019)
Data is a very authentic evidence that need to be saved because the data are at risk of data changes by the party who wanted to misuse the data or no effect on the data. Therefore, so that no unauthorized person to change the existing data, stored or can take the data that is very important, we need a method to be able to secure and keep data. The database is used to keep data and information. The whole system stores the data in the database, so that the contents of stored data security and confidentiality must be maintained. To maintain the security of a security that is required cryptography. With the use of databases that are in can be connected to each other, Database is not just a place to store data,Computer security system is needed at this time in line with the increase use of computers in the world. So existing data security has become seriously threatened to be accessed by people who are not responsible. Computer security becomes very important at this time because it is related to the privacy, integrity, authentication and confidentiality. Thus data need to be stored by using the correct storage techniques, so that the confidentiality and security of data is maintained. Cryptographic techniques with engineering data encryption on the database is one solution that can be used to meet the confidentiality and Data Security settings. With the existence of a cryptography that includes the encryption process, the data in the database can be encoded so that unauthorized persons can not read the information, in addition to those who know the key to describing it. Security of data / information document with a cryptographic technique that uses the Blowfish algorithm chosen method for cryptographic key modernmerupakan shaped symmetric block cipher. Blowfish algorithm which can encrypt text built in text form. Encryption is done using a specific key, resulting ciphertext that can not be understood. The ciphertext can be changed back as the beginning if the decryption using the same key in the beginning when the database mengekripsi.